The impact of common co-morbidities (as measured using the Charlson index) on hip fracture risk in elderly men: a population-based cohort study. - Reyes, C; Estrada, P; Nogués, X; Orozco, P; Cooper, C; Díez-Pérez, A; Formiga, F; Mácias, J; Prieto-Alhambra, D (Springer-Verlag London Ltd, 2014)
UNLABELLED: We used a large population-based health care database to determine the impact of common co-morbidities on hip fracture risk amongst elderly men. We demonstrated that diabetes, chronic obstructive pulmonary disease, renal failure, HIV infection, dementia, and cerebrovascular disease are independent predictors of hip fracture, as is a Charlson score of ≥ 3. INTRODUCTION: Risk factors for hip fractures in men are still unclear. We aimed to identify common co-morbidities (amongst those in the Charlson index) that confer an increased risk of hip fracture amongst elderly men. METHODS: We conducted a population-based cohort study using data from the SIDIAP (Q) database. SIDIAP(Q) contains primary care and hospital inpatient records of a representative 30% of the population of Catalonia, Spain (>2 million people). All men aged ≥ 65 years registered on 1 January 2007 were followed up until 31 December 2009. Both exposure (co-morbidities in the Charlson index) and outcome (incident hip fractures) were ascertained using ICD codes. Poisson regression models were fitted to estimate the effect of (1) each individual co-morbidity and (2) the composite Charlson index score, on hip fracture risk, after adjustment for age, body mass index, smoking, alcohol drinking, and use of oral glucocorticoids. RESULTS: We observed 186,171 men for a median (inter-quartile range) of 2.99 (2.37-2.99) years. In this time, 1,718 (0.92%) participants had a hip fracture. The following co-morbidities were independently associated with hip fractures: diabetes mellitus, chronic obstructive pulmonary disease (COPD), renal failure, HIV infection, dementia, and cerebrovascular disease. A Charlson score of ≥ 3 conferred an increased hip fracture risk. CONCLUSION: Common co-morbidities including diabetes, COPD, cerebrovascular disease, renal failure, and HIV infection are independently associated with an increased risk of hip fracture in elderly men. A Charlson score of 3 or more is associated with a 50% higher risk of hip fracture in this population.